Studies of hadronic event structure in e+e− annihilation from 30 to 209 GeV with the L3 detector - Dova, María Teresa (2004)
In this Report, QCD results obtained from a study of hadronic event structure in high energy e+e− interactions with the L3 detector are presented. The operation of the LEP collider at many different collision energies from 91 to 209 GeV offers a unique opportunity to test QCD by measuring the energy dependence of different observables. The main results concern the measurement of the strong coupling constant, αs, from hadronic event shapes and the study of effects of soft gluon coherence in chargedparticle multiplicity andmomentum distributions.